2021
DOI: 10.2298/jmmb190510014v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical composition and T6 heat treatment on the mechanical properties and fracture behaviour of Al-Si alloys for IC engine components

Abstract: Microstructural examinations of Al-Si alloys intended to manufacture IC engine components revealed a complex phase composition in all samples. Polyhedral crystals of primary silicon were detected in Al-12.5Si alloy, besides the ?-Al phase, eutectic silicon, and several intermetallic phases, identified in the cast samples of both alloys. Better tensile properties were found for samples of Al-11Si. Predominantly intercrystalline fracture with features of ductile failure was observed in both all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For comparison, 232 MPa was obtained by authors of the publication [ 50 ], solution treatment of the AlSi11alloy was performed for 6 h at temperatures lower with 25 degrees, and artificial ageing it at 205 °C for 7 h. Instead, Pedersen [ 51 ] had received maximal strength amounting to 260 MPa for the AlSi10Mg alloy as early as after 60 min of solution treatment at 540 °C, and 4 h of artificial ageing at 150 °C, while a longer time of the treatment did not lead to increasing the UTS . Much lower ultimate tensile strength (215–230 MPa) had been received by authors of the study [ 52 ] in case of the 314.0 alloy after extension of the solution treatment time to 8 h, reduced solution treatment temperature (510 °C) and after artificial ageing at a temperature of 155–240 °C for 5 h. Ammar et al [ 53 ] solution treatment the same alloy with addition of 0.4% Mg at temperature 495 °C for 4 h and quenching in hot water (60 °C), and next, naturally ageing, it had received UTS similar to the one obtained by Pedersen [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, 232 MPa was obtained by authors of the publication [ 50 ], solution treatment of the AlSi11alloy was performed for 6 h at temperatures lower with 25 degrees, and artificial ageing it at 205 °C for 7 h. Instead, Pedersen [ 51 ] had received maximal strength amounting to 260 MPa for the AlSi10Mg alloy as early as after 60 min of solution treatment at 540 °C, and 4 h of artificial ageing at 150 °C, while a longer time of the treatment did not lead to increasing the UTS . Much lower ultimate tensile strength (215–230 MPa) had been received by authors of the study [ 52 ] in case of the 314.0 alloy after extension of the solution treatment time to 8 h, reduced solution treatment temperature (510 °C) and after artificial ageing at a temperature of 155–240 °C for 5 h. Ammar et al [ 53 ] solution treatment the same alloy with addition of 0.4% Mg at temperature 495 °C for 4 h and quenching in hot water (60 °C), and next, naturally ageing, it had received UTS similar to the one obtained by Pedersen [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In case of the hardness, similarly like in case of the tensile strength, the main role is played by high temperature of the solution treatment (20–30 °C below the eutectic temperature) and low artificial ageing treatment temperature (165 °C) responsible for suitable dispersion degree of precipitations strengthening the alloy. The decrease in the hardness values after the T6 heat treatment can also result from the wide dispersion of eutectic silicon particles [ 50 ]. Moreover, according to Iskah et al [ 69 ] area of widely dispersed particles of the silicon is smaller, from its availability for the measuring the intended point of view, comparing to the area of the soft phase α(Al), which results in the lower values of the hardness of the test piece.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the modified alloys, especially, the B390-P-Bi alloy presenting many finer dimples, were observed on the fracture surfaces. Vuksanovic et al (2021) [51] and Xiao et al (2023) [52] indicated that dimples on fracture surfaces were present after the T6 heat treatment and they were significant on the surfaces of the Al-12.5Si alloy and Al-Si-Cu-Mg-Ni-Cr. Due to the rounding and coarsening of eutectic silicon phase, there was increased resistance to fracture.…”
Section: Fracture Surfacesmentioning
confidence: 99%